1990
DOI: 10.1016/0304-3959(90)90049-j
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of opioid analgesia in humans after intravenous bolus administration: alfentanil, fentanyl and morphine compared on experimental pain

Abstract: This report examines the relationship of plasma drug concentration to analgesic effect following bolus doses of alfentanil, fentanyl and morphine and assesses individual differences in analgesic response among volunteers. We predicted that the 3 opioids would yield disparate analgesic profiles because their physicochemical and pharmacokinetic characteristics differ. Ten healthy volunteers received intravenous bolus doses of either alfentanil, fentanyl, morphine or normal saline on different days. We stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 15 publications
5
39
0
Order By: Relevance
“…Electrically-induced pain in the teeth and skin has been assessed by electroencephalogram (EEG) recordings. This type of pain assessment showed opioid analgesia in accordance with the psychophysical pain scoring [51,86].…”
Section: Figuresupporting
confidence: 60%
See 3 more Smart Citations
“…Electrically-induced pain in the teeth and skin has been assessed by electroencephalogram (EEG) recordings. This type of pain assessment showed opioid analgesia in accordance with the psychophysical pain scoring [51,86].…”
Section: Figuresupporting
confidence: 60%
“…Electrical pain was unaffected in one study, whereas two studies found an effect on this pain modality [58][59][60]. Furthermore electrical dental pain has been tested and found to be attenuated by fentanyl [51,61]. Heat pain has been tested through various stimulation paradigms and conflicting results exist.…”
Section: Fentanyl (Table 3)mentioning
confidence: 99%
See 2 more Smart Citations
“…Oral morphine and hydromorphone are primarily metabolized in the liver through the uridine-diphosphoglucuronosyltransferase (UGT) system [68]. Fentanyl [69] and methadone [70] are metabolized by the CYP3A4 enzyme, which is responsible for the complete or partial metabolism of 50% of all known drugs. Genetic variation in CYP2D6 results in poor metabolism of the opioid codeine to its active metabolite morphine [66,71].…”
Section: Opioid Metabolismmentioning
confidence: 99%